The Influence of Counseling Services on Students' Learning Motivation - Ferry Setiawan Budi; Christopher Cahyadi (International Perspectives in Christian Education and Philosophy, 2025)
Analyzing how counseling services affect students' motivation to learn is the goal of this study. A quasi-experimental design with control and experimental groups is the methodology employed. Questionnaires completed both before (pre-test) and after (post-test) the treatment were used to collect data. According to the study's findings, students who receive counseling services report feeling far more motivated to learn. With an average rise of 12.78%, the average learning motivation score rose from 55.91% (low category) to 68.70% (high category). Wilcoxon test statistical analysis supports these findings, demonstrating that counseling services have a significant impact on students' increased drive to learn (p < 0.05). The utilization of counseling services as a successful strategy to increase students' motivation to learn is one area in which this research greatly contributes to the field of education. Students who lack motivation to learn can benefit from this in order to enhance their academic performance.